2014
DOI: 10.3892/mmr.2014.2842
|View full text |Cite
|
Sign up to set email alerts
|

Protection of cultured human hepatocytes from hydrogen peroxide-induced apoptosis by relaxin-3

Abstract: Previous studies have suggested that hepatocyte apoptosis may be a fundamental underlying mechanism of liver injury and diseases, such as liver fibrosis. Relaxin‑3 has been reported to have anti‑fibrotic actions in the heart and to attenuate isoproterenol‑induced myocardial injury; however, the beneficial role of relaxin‑3 on hepatocyte apoptosis remains to be elucidated. The aim of the present study was to explore the role and possible mechanisms of relaxin‑3 through hydrogen peroxide (H2O2)‑induced apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Oxidative stress from ROS production also contributes to graft injury because it is detrimental to liver parenchymal cell survival. 24 , 32 , 33 These results expand on previous findings of M1 macrophages initiating and sustaining IRI pathology. 18 , 34 …”
Section: Discussionsupporting
confidence: 85%
“…Oxidative stress from ROS production also contributes to graft injury because it is detrimental to liver parenchymal cell survival. 24 , 32 , 33 These results expand on previous findings of M1 macrophages initiating and sustaining IRI pathology. 18 , 34 …”
Section: Discussionsupporting
confidence: 85%
“…Some studies suggested that relaxin-3 was involved in modulating brain function in combination with RXFP3 [15], and one study showed that relaxin-3 exerts its effects by binding to RXFP1 (the primary relaxin-2 receptor) [16]. Our previous studies demonstrated that relaxin-3 may attenuate hepatocyte apoptosis and protect against liver injury by inhibiting endoplasmic reticulum stress [13]. We found that plasma relaxin-3 levels were not significantly different between patients with liver cirrhosis and control subjects, however, plasma relaxin-2 concentrations were significantly positively correlated with relaxin-3 concentrations in patients with liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…A single adenoviral delivery of relaxin-2 in the liver attenuated established hepatic fibrosis by suppressing collagen crosslinking and enhancing collagen degradation [12]. Our previous study showed that relaxin-3, the 'ancestral' member of the relaxin peptide family, inhibits ROS-induced hepatic cell apoptosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…H 2 O 2 is a potent oxidant, and studies have shown that H 2 O 2 can induce hepatocyte apoptosis ( 48 , 49 ). In the present study, LPS and D-GalN did not exert a significant effect on the proliferation of the BRL liver cell line (data not shown).…”
Section: Discussionmentioning
confidence: 99%